AGE/RAGE-Induced EMP Release via the NOX-Derived ROS Pathway - Ying-Hua Chen; Zhang-Wei Chen; Hong-Mei Li; Xin-Feng Yan; Bo Feng (Journal of Diabetes Research)
Objective. Diabetes is associated with accelerated formation of advanced glycation end products (AGEs) that are extensively found in circulating endothelial microparticles (EMPs). This study aimed to investigate whether AGEs have a direct effect on EMP formation and the possible underlying mechanism. Methods. In vitro, cultured human umbilical vein endothelial cells (HUVECs) were incubated with AGEs (200 and 400 μg/ml) for 24 hours with or without pretreatment with anti-RAGE antibody, NOX inhibitor, or ROS scavenger. The number of CD31-positive EMPs was assessed by flow cytometry. Results. The number of EMPs was significantly increased in HUVECs stimulated by AGEs in a dose-dependent manner. In addition, receptors for AGEs (RAGE), NAD(P)H oxidase (NOX), and reactive oxygen species (ROS) were increased by AGEs as compared to the control group. These changes could be reversed when HUVECs were pretreated with anti-RAGE antibody. Moreover, inhibition of NOX as well as antioxidant treatment reduced the release of EMPs induced by AGEs. Conclusion. Our study suggested that AGEs increased EMP generation, which was mediated by RAGE signaling through NOX-derived ROS.